On the Body of the Lord - Albertus, Magnus, Saint, 1193?-1280 (Book collections on Project MUSE., 2017)
"Albert the Great wrote On the Body of the Lord in the 1270s, making it his final work of sacramental theology. A companion volume to his commentary on the Mass, On the Body of the Lord is a comprehensive discussion of Eucharistic theology. The treatise is structured around six names for the Eucharist taken from the Mass: grace, gift, food, communion, sacrifice, and sacrament. It emerges from the liturgy and is intended to draw the reader back to worship. The overall movement of the treatise follows the order of God's wisdom. Albert begins by discussing the Eucharist as a gift flowing from the goodness of the Trinity. He touches on its relation to redemption and the Church, including a rigorous Aristotelian analysis of Eucharistic change and presence before ending with a discussion of Mass rubrics. The most significant theological emphasis is on the Eucharist as food given to feed the people of God."--